Analisis Pemanfaatan Fasilitas Perpajakan Pada Yayasan Khusus Bidang Pendidikan Dalam Efisensi Pajak Penghasilan - N Heriyah; Elok Faiqoh Himah (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
This study uses a qualitative method with a case study approach at a foundation that specializes in "X" Education and conducts direct observations in the field by reviewing the data that has been collected from observations, interviews, to tax accounting data collection. The results showed that to analyze the use of tax facilities in terms of excess remaining and taking into account the present value, the results obtained in the fourth alternative, namely the use of excess remaining in the fourth year which resulted in a higher tax benefit value of 30% of expenses. income tax or Rp. 23,203,311. If the present value is not considered, then the 1st to 4th alternative yields the same tax benefit, namely 25% of the income tax expense or Rp. 8,238,732. If the Foundation engaged in Education X does not implement and comply with all the provisions and procedures set forth in the provisions of Per-44/Per/2009, there will be a risk of failure in the utilization of tax facilities. The maximum risk that may arise as a result of failure to use the X Education Foundation tax facility is 5% or Rp. 4,103,366 of income tax expense.